Malaysian Politics under Mahathir. - Milne, R. S.; Mauzy, Diane K. (New York : Florence :: Routledge: Taylor & Francis Group Distributor, 1999)
Annotation Since Mahathir Mohamad became prime minister in 1981, the Malaysian economy has grown dramatically under his authoritarian government and Mahathir has remained firmly in control of the political scene. This work provides an account of his character, ideas, and temperament, and looks at the social and political scene in Malaysia. It examines Mahathir's successes as well as his faults and assesses their implications, and considers the impact on Malaysia of the recent economic crisis in Asia. Milne has held professorships at the University of British Columbia, Singapore University, London University, and Victoria University, New Zealand. Mauzy is a professor of political science at the University of British Columbia. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Trade Routledge.
Keywords: Malaysia -- -- Politics and Government